Analysis on Credit Risk Assessment for Accounts Receivable Supply Chain Financing Based on Credit Insurance - Bi Keran (E3S Web of Conferences, 2021)
This paper studies the model of accounts receivable supply chain financing based on credit insurance from the perspective of banks. First of all, the paper analyzes two different financing modes of the innovative model - the pledge financing mode and the factoring financing mode. Secondly, the paper explains the sources of credit risks for accounts receivable supply chain financing under credit insurance, and the necessity of using credit insurance. The sources of credit risks mainly include: the enterprises’ comprehensive strength under systemic and non-systemic risks, status of accounts receivable, supply chain operation, performance of insurance companies, and so on. In addition, based on the credit risks explained in this paper, the risk assessment system and the credit risk assessment model are built. At the end, the paper offers three suggestions for the banks’ financing risk control: bank should carefully check the policy’s exclusions clauses; bank must carefully check the authenticity of accounts receivable; bank can use dynamic monitoring on qualification checking for financing enterprises, core enterprises and insurance companies.